Evaluation of Low Cost Digital Cameras for Producing Photogrammetric Output from UAV - Sukor, Syafiq; Ahmad, Anuar (International Journal of Engineering and Technology, 2018)
Recently there a lot of improvement in digital photogrammetry and this allow photogrammetry to become faster and cheaper . This study discuss about two type of low cost camera which is the compact camera (Canon Power Shot SX230 ) and action camera (Xiaomi yi) where both of them have different lens distortion. This study is conducted within UTM (Universiti Teknologi Malaysia) Skudai campus at KolejÂ Tun Razak. Both of the Canon Power Shot SX230 and Xiaomi yi camera would be attach to the UAVÂ to take aerial photo with three different altitude which is 60 meter, 80 meter and 100 meter with a similar flight path. Check point (CPs) and Ground control point (GCPs) were also established using rapid static technique of Global Positioning System (GPS) and Total Station. The Canon Power Shot SX230 and Xiaomi yi camera is then calibrated using checkboard calibration this is done by using AgisoftÂ Lens software. Then all of the pictures that been taken by the Canon Power Shot SX230 and the Xiaomi yi would be processed by using Agisoft Photoscan software to generate Digital Elevation Model (DEM), orthophoto and contour line. The accuracy of DEM was determined based on Root Mean Squared Error (RMSE) value. Both of the result is then analyze visually and statically. Overall both of the camera gives a slight different in accuracy.Â